Comparative Analysis of Decentralization and Power Distribution in Local Self-Government: Kazakhstan and Europe - Kuanysh Sabitov; Gulnar Alibayeva; Erkinbek Rakimbayev; Kabdulsamikh Aitkhozhin; Yerzat Bekbayev (Khazanah Hukum, 2025)
The aim of the article is to identify the key problems of decentralization of power in Kazakhstan, to analyze foreign experience on the example of Poland and Spain, and to formulate specific steps for the implementation of the most successful European practices in Kazakhstan. Poland is interesting as an example of a successful departure from the post-socialist model of decentralization. Spain is chosen as an example of a unitary state with significant local autonomy. The analysis of these countries revealed the advantages of their models, but also found certain problems. Nevertheless, the author believes that their experience can be used to build an effective model of decentralization in the Republic of Kazakhstan and provides specific examples of the implementation of their experience in Kazakhstan. Based on the comparative analysis, the author formulates a number of legal and practical recommendations. The article also addresses institutional constraints and socio-political factors that may affect the adaptability of foreign models to Kazakhstan’s context, emphasizing the importance of gradual, context-sensitive reform.